High-temperature-resistant electrolytic copper foil as well as preparation method and application thereof
By optimizing the preparation method and components of electrolytic copper foil, using multi-stage electrolytic process and specific antioxidant and heat-resistant layer treatment, the mechanical strength reduction of electrolytic copper foil under high temperature conditions is solved, and its high-temperature peel strength is significantly improved , meets the requirements of the electronics industry for high heat resistance.
Patent Information
- Application Number
- CN202411867461.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-02-07
AI Technical Summary
The existing electrolytic copper foil softens under high temperature conditions, resulting in a decrease in mechanical strength, affecting the life of electronic components, and its heat resistance is insufficient, making it difficult to meet the electronic industry's requirements for high heat resistance.
By optimizing the preparation method and components, a multi-stage electrolysis process is adopted, including acidification, coarseness, curing, antioxidant, heat resistance, hot water washing and coupling processes, using benzotriazole and barium dinonylnaphthalenesulfonate. With tocopherol as antioxidant layer, zinc, nickel, platinum and tantalum form a quad-alloy heat-resistant layer, and dodecyl trimethylammonium chloride and gamma-glycidyl etheroxypropyl trimethoxysilane as the joints. Coupling agent improves the high-temperature peel resistance of electrolytic copper foil.
It significantly improves the normal temperature resistance of electrolytic copper foil and its high temperature peel strength, which meets the requirements of the electronics industry for high heat resistance, and alleviates cost pressure.
Smart Images

Figure BDA0005194800380000131 
Figure BDA0005194800380000141
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper foil, and in particular to a high temperature resistant electrolytic copper foil and a preparation method and application thereof. Background Art
[0002] With the development of electronic information technology, the application fields of electronic components are becoming more and more extensive, and the performance requirements for electronic components are becoming higher and higher. As a provider of electrical connections for electronic components, printed circuit boards (PCBs) occupy an important position in the electronics industry. Copper metal has good conductivity and can carry charges without losing signals. The metal foil made of it, as an important component of printed circuit boards, determines the performance of signal transmission.
[0003] Electrolytic copper foil is used in various fields, including rigid printed circuit boards, flexible printed circuit boards, and electromagnetic shielding materials. In printed circuit boards, when the electrolytic copper foil and the insulating layer are bonded to form the material, the processing temperature is high and exceeds 250°C. The electrolytic copper foil subjected to the high temperature load softens and the mechanical strength decreases, which in turn causes various problems. When the electrolytic copper foil is used as the negative electrode current collector of the lithium-ion secondary battery, when a mixture layer containing the negative electrode active material is formed on the surface of the electrolytic copper foil, there is a high temperature load of about 300°C. The electrolytic copper foil used for the negative electrode current collector will soften, and the resistance to expansion and contraction during charging and discharging will be reduced, thereby reducing the life of the lithium-ion secondary battery. This requires the electrolytic copper foil to have higher performance, especially for the requirements of heat resistance and oxidation resistance. However, the electrolytic copper foil prepared by the current production method of electrolytic copper foil cannot meet the requirements of heat resistance, and usually relies on imported copper foil. Therefore, the development of an electrolytic copper foil with high heat resistance is of great significance to the rapid development of the electronics industry.
[0004] Chinese patent CN105154927A discloses a surface treatment process for electrolytic copper foil, which is characterized in that the process first undergoes pretreatment, then uses multiple fractal electrodeposition of copper, and finally completes the surface treatment through passivation coating, including: original foil-pretreatment-fractal electrodeposition of copper-water washing-galvanizing treatment-water washing-passivation-organic film coating-drying-surface treatment. However, the heat resistance of the copper foil generally obtained is still insufficient, and it is easy to fall off during the subsequent processing, and further improvement is needed.
[0005] Chinese patent CN116791160B discloses a method for preparing a high heat-resistant electrolytic copper foil, comprising the following steps: using electrolytic copper foil as a raw material, and sequentially performing a first roughening, a first curing, a second roughening, a second curing, a third roughening, and a third curing; wherein the Cu in the electrolyte used for each roughening and curing is 2+The concentration of H2SO4 decreases in turn. By controlling the gradient change of copper and sulfuric acid concentrations in the roughening and curing copper foil, and using additives, the obtained copper foil has excellent adhesion to the epoxy substrate. It not only has good peel strength at room temperature, but also maintains high peel strength at high temperature, which better meets the subsequent thermal processing of the copper clad laminate. However, its high temperature peel strength is 1.48N / mm, which is 92% of the normal temperature peel strength, which is still not ideal.
[0006] At present, electrolytic copper foil has three main defects. First, the heat-resistant layer and corrosion-resistant layer of electrolytic copper foil are two-layer structures, which are usually prone to peeling, affecting the practical application of electrolytic copper foil. Second, its high-temperature peeling strength needs to be further improved.
[0007] Based on this, developing an electrolytic copper foil and its preparation method, optimizing the preparation method and components, and improving its high-temperature peeling strength are the research focuses of researchers in this field. Summary of the invention
[0008] In view of the above problems, the present invention provides a high temperature resistant electrolytic copper foil and a preparation method thereof, and improves the high temperature peeling strength of the foil by optimizing the preparation method and components.
[0009] To achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0010] On the one hand, the present invention provides a method for preparing a high-temperature resistant electrolytic copper foil, comprising a roughening process, a curing process, an anti-oxidation process, a heat-resistant process, a hot water washing process and a coupling process; wherein the electrolyte of the anti-oxidation process comprises benzotriazole, barium dinonylnaphthalenesulfonate and tocopherol, and the mass ratio of the three is 1-3:0.8-1.5:0.1-1.
[0011] Preferably, the roughening process includes primary roughening and secondary roughening;
[0012] Preferably, the process parameters of the primary roughening are: in the electrolyte, Cu 2+ Concentration 20-30g / L, H2SO4 concentration 190-210g / L, temperature 20-25℃, current density 800-1200A / m 2 , time is 4-6s.
[0013] Further preferably, the process parameters of the primary roughening are: in the electrolyte, Cu 2+ Concentration 22-28g / L, H2SO4 concentration 200-208g / L, temperature 22-25℃, current density 800-1000A / m 2 , time is 4-5s.
[0014] More preferably, the process parameters of the primary roughening are: in the electrolyte, Cu 2+ Concentration 26g / L, H2SO4 concentration 205g / L, temperature 23℃, current density 900A / m 2 , time is 5s.
[0015] Preferably, the process parameters of the secondary roughening are: in the electrolyte, Cu 2+ Concentration 20-30g / L, H2SO4 concentration 190-210g / L, temperature 20-25℃, current density 500-800A / m 2 , time is 1-3s.
[0016] Further preferably, the process parameters of the secondary roughening are: in the electrolyte, Cu 2+ Concentration 22-28g / L, H2SO4 concentration 200-208g / L, temperature 22-25℃, current density 500-600A / m 2 , time is 1-2s.
[0017] More preferably, the process parameters of the secondary roughening are: in the electrolyte, Cu 2+ Concentration 26g / L, H2SO4 concentration 205g / L, temperature 23℃, current density 600A / m 2 , time is 2s.
[0018] Preferably, the curing process includes primary curing and secondary curing.
[0019] Preferably, the process parameters of the primary curing are: in the electrolyte, Cu 2+ Concentration 35-42g / L, H2SO4 concentration 140-160g / L, temperature 20-25℃, current density 800-1000A / m 2 , time is 4-6s.
[0020] Further preferably, the process parameters of the primary curing are: in the electrolyte, Cu 2+ Concentration 35-40g / L, H2SO4 concentration 140-150g / L, temperature 20-23℃, current density 800-900A / m 2 , time is 4-5s.
[0021] More preferably, the process parameters of the primary curing are: in the electrolyte, Cu 2+ Concentration 38g / L, H2SO4 concentration 148g / L, temperature 23℃, current density 850A / m 2 , time is 5s.
[0022] Preferably, the process parameters of the secondary curing are: in the electrolyte, Cu 2+ Concentration 35-42g / L, H2SO4 concentration 140-160g / L, temperature 20-25℃, current density 500-600A / m 2 , time is 1-3s.
[0023] Further preferably, the process parameters of the secondary curing are: in the electrolyte, Cu 2+ Concentration 35-40g / L, H2SO4 concentration 140-150g / L, temperature 20-23℃, current density 550-600A / m 2 , time is 1-2s.
[0024] More preferably, the process parameters of the secondary curing are: in the electrolyte, Cu 2+ Concentration 38g / L, H2SO4 concentration 148g / L, temperature 23℃, current density 550A / m 2 , time is 2s.
[0025] Preferably, the mass ratio of benzotriazole, barium dinonylnaphthalenesulfonate and tocopherol is 1.2-2:0.8-1.52:0.2-0.6.
[0026] More preferably, the mass ratio of benzotriazole, barium dinonylnaphthalenesulfonate and tocopherol is 1.5:1:0.5.
[0027] Preferably, the process parameters of the antioxidant step are: in the electrolyte, benzotriazole 2-5 g / L, barium dinonylnaphthalenesulfonate 1-3 g / L, tocopherol 0.1-1.5 g / L, pH 4-8, temperature 30-45 ° C, current density 300-500 A / m 2 , time is 1-3s.
[0028] Further preferably, the process parameters of the antioxidant step are: in the electrolyte, benzotriazole 2-3 g / L, barium dinonylnaphthalenesulfonate 1.5-2.5 g / L, tocopherol 0.5-1.2 g / L, pH 5-7, temperature 35-45 ° C, current density 350-500 A / m 2 , time is 1-2s.
[0029] More preferably, the process parameters of the antioxidant step are: in the electrolyte, 3 g / L benzotriazole, 2 g / L barium dinonylnaphthalenesulfonate, 1 g / L tocopherol, pH 6, temperature 40°C, current density 450 A / m 2 , time is 2s.
[0030] Preferably, in the heat-resistant process, a heat-resistant layer is formed by zinc, nickel, platinum and tantalum in the electrolyte.
[0031] Preferably, the mass ratio of zinc, nickel, platinum and tantalum is 8-12:6-10:0.05-0.2:0.05-0.2.
[0032] Further preferably, the mass ratio of zinc, nickel, platinum and tantalum is 8-10:6-8:0.05-0.1:0.05-0.1.
[0033] More preferably, the mass ratio of zinc, nickel, platinum and tantalum is 10:8:0.1:0.1.
[0034] Preferably, the process parameters of the heat-resistant process are: in the electrolyte, Zn 2+ 3-8g / L, Ni 2+ 1-6g / L, Pt 2+ 0.01-0.1g / L, Ta 5+ 0.01-0.1g / L, pH 7-9, temperature 30-45℃, current density 140-220A / m 2 , time is 1-3s.
[0035] Further preferably, the process parameters of the heat-resistant process are: in the electrolyte, Zn 2+ 4-6g / L, Ni 2+ 2-4g / L, Pt 2+ 0.02-0.06g / L, Ta 5+ 0.02-0.06g / L, pH 7-8, temperature 30-45℃, current density 140-200A / m 2 , time is 2-3s.
[0036] More preferably, the process parameters of the heat-resistant process are: in the electrolyte, Zn 2+ 5g / L, Ni 2+ 4g / L, Pt 2+ 0.05g / L,Ta 5+ 0.05g / L, pH 8, temperature 40°C, current density 180A / m 2 , time is 2s.
[0037] Preferably, the process parameters of the hot water washing step are: temperature 60-80°C, pressure 0.5-1MPa.
[0038] Further preferably, the process parameters of the hot water washing step are: temperature 60° C., pressure 0.5 MPa.
[0039] Preferably, the coupling agent in the coupling step is a silane coupling agent.
[0040] More preferably, the silane coupling agent is selected from at least one of phenyltriethoxysilane and γ-glycidyloxypropyltrimethoxysilane.
[0041] More preferably, the silane coupling agent is phenyltriethoxysilane and γ-glycidyloxypropyltrimethoxysilane.
[0042] Preferably, the mass ratio of phenyltriethoxysilane to γ-glycidyloxypropyltrimethoxysilane is 1-2:0.8-1.2.
[0043] Further preferably, the mass ratio of phenyltriethoxysilane to γ-glycidyloxypropyltrimethoxysilane is 1.5-2:0.8-1.
[0044] More preferably, the mass ratio of phenyltriethoxysilane to γ-glycidyloxypropyltrimethoxysilane is 2:1.
[0045] Preferably, the concentration of the silane coupling agent is 0.3%-0.4%. More preferably, the concentration of the silane coupling agent is 0.32%.
[0046] Preferably, the preparation method further comprises acidification before the roughening step.
[0047] Preferably, the process parameters of the acidification are: H2SO4 concentration in the electrolyte is 140-190 g / L, the temperature is 30-40°C, and the time is 1-3 s.
[0048] Further preferably, the process parameters of the acidification are: H2SO4 concentration in the electrolyte is 140-180 g / L, the temperature is 30-35°C, and the time is 1-2 s.
[0049] More preferably, the process parameters of the acidification are: H2SO4 concentration in the electrolyte is 160g / L, the temperature is 30°C, and the time is 2s.
[0050] Preferably, the preparation method further comprises drying.
[0051] Preferably, the drying is performed after the coupling step, and the process parameters are: temperature 100-150°C.
[0052] On the other hand, the present invention provides a high temperature resistant electrolytic copper foil prepared by the above-mentioned preparation method.
[0053] In another aspect, the present invention provides the use of the high temperature resistant electrolytic copper foil prepared by the above-mentioned preparation method in a printed circuit board.
[0054] Compared with the prior art, the present invention has the following beneficial effects:
[0055] 1. The present invention optimizes the antioxidant layer treatment and uses benzotriazole, barium dinonylnaphthalenesulfonate and tocopherol as the antioxidant layer. It is found that the three have a synergistic effect and significantly improve the room temperature and high temperature oxidation resistance of the obtained electrolytic copper foil and its high temperature peeling strength under a specific ratio.
[0056] 2. The present invention optimizes the heat-resistant layer treatment to form a quaternary alloy heat-resistant layer with zinc, nickel, platinum and tantalum. The researchers found that only a small amount of rare precious metals, platinum and tantalum, can be added to form a synergistic effect with zinc and nickel. Under a specific ratio, not only can the room temperature and high temperature oxidation resistance of the obtained electrolytic copper foil, as well as its high temperature peeling strength be significantly improved, but also the cost pressure can be alleviated.
[0057] 3. The present invention uses dodecyltrimethylammonium chloride and γ-glycidyloxypropyltrimethoxysilane as coupling agents, and under a specific ratio, the various combinations of the electrolytic copper foil are more tightly bonded and the anti-peeling strength is stronger.
[0058] 4. In summary, the specific components, proportions and preparation methods of the present invention significantly improve the room temperature and high temperature oxidation resistance of the obtained electrolytic copper foil, as well as its high temperature peeling strength, and better meet the requirements of the field for high heat resistance of the electrolytic copper foil. DETAILED DESCRIPTION
[0059] In order to make the technical means, creative features, purpose and effect of the present invention easy to understand, the present invention is further explained below in conjunction with specific embodiments, but the following embodiments are only preferred embodiments of the present invention, not all. Based on the embodiments in the implementation mode, other embodiments obtained by those skilled in the art without making creative work all belong to the protection scope of the present invention. It is worth noting that the raw materials used in the present invention are all common commercial products, and their sources are not specifically limited. The technology and scientific terms used in the embodiments have the meanings commonly understood by those of ordinary skill in the art to which the present invention belongs.
[0060] Example 1
[0061] A high temperature resistant electrolytic copper foil, the preparation method is as follows:
[0062] The electrolytic process is used to prepare the 13-14μm rough foil, and then different electrolyte combinations and electrodeposition process parameters are used in the electrolytic equipment in multiple stages to treat the surface of the electrolytic copper foil: including acidification, roughening process, curing process, anti-oxidation process, heat-resistant process, hot water washing process, coupling process and drying. The process flow is as follows:
[0063] S0: The process parameters of acidification are: H2SO4 concentration in the electrolyte is 160g / L, the temperature is 30℃, and the time is 2s.
[0064] S1: The process parameters of the primary roughening are: in the electrolyte, Cu 2+ Concentration 26g / L, H2SO4 concentration 205g / L, temperature 23℃, current density 900A / m 2 , time is 5s.
[0065] S2: The process parameters of the secondary roughening are: in the electrolyte, Cu 2+ Concentration 26g / L, H2SO4 concentration 205g / L, temperature 23℃, current density 600A / m 2 , time is 2s.
[0066] S3: The process parameters of primary curing are: in the electrolyte, Cu 2+ Concentration 38g / L, H2SO4 concentration 148g / L, temperature 23℃, current density 850A / m 2 , time is 5s.
[0067] S4: The process parameters of secondary curing are: in the electrolyte, Cu 2+ Concentration 38g / L, H2SO4 concentration 148g / L, temperature 23℃, current density 550A / m 2 , time is 2s.
[0068] S5: The process parameters of the antioxidant process are: in the electrolyte, benzotriazole 3g / L, barium dinonylnaphthalenesulfonate 2g / L, tocopherol 1g / L, pH 6, temperature 40°C, current density 450A / m 2 , time is 2s.
[0069] S6: The process parameters of the heat-resistant process are: in the electrolyte, Zn 2+ Concentration 5g / L, Ni 2+ Concentration 4g / L, Pt 2+ Concentration 0.05g / L, Ta 5+ Concentration 0.05g / L, pH 8, temperature 40°C, current density 180A / m 2 , time is 2s.
[0070] S7: The process parameters of the hot water washing process are: temperature 60°C, pressure 0.5MPa.
[0071] S8: Coupling process: Phenyl triethoxysilane and γ-glycidyloxypropyl trimethoxysilane are mixed at a mass ratio of 2:1 to prepare a 0.32 wt % solution. The surface of the copper foil treated with the anti-oxidation layer is sprayed with the silane coupling agent aqueous solution.
[0072] S9: Drying: Drying at a temperature of 100-150°C for 3s to obtain a finished foil.
[0073] Example 2
[0074] A high temperature resistant electrolytic copper foil, the preparation method is as follows:
[0075] The electrolytic process is used to prepare the 13-14μm rough foil, and then different electrolyte combinations and electrodeposition process parameters are used in the electrolytic equipment in multiple stages to treat the surface of the electrolytic copper foil: including acidification, roughening process, curing process, anti-oxidation process, heat-resistant process, hot water washing process, coupling process and drying. The process flow is as follows:
[0076] S0: The process parameters of acidification are: H2SO4 concentration in the electrolyte is 140g / L, the temperature is 35℃, and the time is 2s.
[0077] S1: The process parameters of the primary roughening are: in the electrolyte, Cu 2+ Concentration 20g / L, H2SO4 concentration 210g / L, temperature 20℃, current density 1200A / m 2 , time is 4s.
[0078] S2: The process parameters of the secondary roughening are: in the electrolyte, Cu 2+ Concentration 20g / L, H2SO4 concentration 210g / L, temperature 20℃, current density 500A / m 2 , time is 1s.
[0079] S3: The process parameters of primary curing are: in the electrolyte, Cu 2+ Concentration 35g / L, H2SO4 concentration 160g / L, temperature 25℃, current density 1000A / m 2 , time is 4s.
[0080] S4: The process parameters of secondary curing are: in the electrolyte, Cu 2+ Concentration 35g / L, H2SO4 concentration 160g / L, temperature 25℃, current density 600A / m 2 , time is 3s.
[0081] S5: The process parameters of the antioxidant process are: in the electrolyte, benzotriazole 2g / L, barium dinonylnaphthalenesulfonate 1g / L, tocopherol 0.2g / L, pH 6, temperature 45°C, current density 500A / m 2 , time is 3s.
[0082] S6: The process parameters of the heat-resistant process are: in the electrolyte, Zn 2+ Concentration 8g / L, Ni 2+ Concentration 10g / L, Pt 2+Concentration 0.2g / L, Ta 5+ Concentration 0.2g / L, pH 7, temperature 30℃, current density 140A / m 2 , time is 1s.
[0083] S7: The process parameters of the hot water washing process are: temperature 80°C, pressure 1MPa.
[0084] S8: Coupling process: Phenyl triethoxysilane and γ-glycidyloxypropyl trimethoxysilane are mixed at a mass ratio of 1:1.2 to prepare a 0.4 wt % solution. The surface of the copper foil treated with the anti-oxidation layer is sprayed with the silane coupling agent aqueous solution.
[0085] S9: Drying: Drying at 100°C for 3s to obtain a finished foil.
[0086] Example 3
[0087] A high temperature resistant electrolytic copper foil, the preparation method is as follows:
[0088] The electrolytic process is used to prepare the 13-14μm rough foil, and then different electrolyte combinations and electrodeposition process parameters are used in the electrolytic equipment in multiple stages to treat the surface of the electrolytic copper foil: including acidification, roughening process, curing process, anti-oxidation process, heat-resistant process, hot water washing process, coupling process and drying. The process flow is as follows:
[0089] S0: The process parameters of acidification are: H2SO4 concentration in the electrolyte is 180g / L, the temperature is 30℃, and the time is 2s.
[0090] S1: The process parameters of the primary roughening are: in the electrolyte, Cu 2+ Concentration 30g / L, H2SO4 concentration 190g / L, temperature 25℃, current density 800A / m 2 , time is 6s.
[0091] S2: The process parameters of the secondary roughening are: in the electrolyte, Cu 2+ Concentration 30g / L, H2SO4 concentration 190g / L, temperature 25℃, current density 500A / m 2 , time is 3s.
[0092] S3: The process parameters of primary curing are: in the electrolyte, Cu 2+ Concentration 35g / L, H2SO4 concentration 160g / L, temperature 20℃, current density 800A / m 2 , time is 6s.
[0093] S4: The process parameters of secondary curing are: in the electrolyte, Cu2+ Concentration 35g / L, H2SO4 concentration 160g / L, temperature 20℃, current density 500A / m 2 , time is 1s.
[0094] S5: The process parameters of the antioxidant process are: in the electrolyte, benzotriazole 5g / L, barium dinonylnaphthalenesulfonate 3g / L, tocopherol 0.1g / L, pH 8, temperature 30°C, current density 300A / m 2 , time is 1s.
[0095] S6: The process parameters of the heat-resistant process are: in the electrolyte, Zn 2+ Concentration 3g / L, Ni 2+ Concentration 2g / L, Pt 2+ Concentration 0.02g / L, Ta 5+ Concentration 0.02g / L, pH 7, temperature 45°C, current density 220A / m 2 , time is 3s.
[0096] S7: The process parameters of the hot water washing process are: temperature 60°C, pressure 0.5MPa.
[0097] S8: Coupling process: Phenyl triethoxysilane and γ-glycidyloxypropyl trimethoxysilane are mixed at a mass ratio of 2:0.8 to prepare a 0.3 wt % solution. The surface of the copper foil treated with the anti-oxidation layer is sprayed with the silane coupling agent aqueous solution.
[0098] S9: Drying: Drying at 150°C for 3 seconds to obtain a finished foil.
[0099] Comparative Example 1
[0100] A high temperature resistant electrolytic copper foil, the preparation method is as follows:
[0101] The electrolytic process is used to prepare the 13-14μm rough foil, and then different electrolyte combinations and electrodeposition process parameters are used in the electrolytic equipment in multiple stages to treat the surface of the electrolytic copper foil: including acidification, roughening process, curing process, anti-oxidation process, heat-resistant process, hot water washing process, coupling process and drying. The process flow is as follows:
[0102] S0: The process parameters of acidification are: H2SO4 concentration in the electrolyte is 120g / L, the temperature is 40℃, and the time is 3s.
[0103] S1: The process parameters of the primary roughening are: in the electrolyte, Cu 2+ Concentration 18g / L, H2SO4 concentration 180g / L, temperature 30℃, current density 1200A / m 2, time is 5s.
[0104] S2: The process parameters of the secondary roughening are: in the electrolyte, Cu 2+ Concentration 18g / L, H2SO4 concentration 180g / L, temperature 30℃, current density 200A / m 2 , time is 5s.
[0105] S3: The process parameters of primary curing are: in the electrolyte, Cu 2+ Concentration 45g / L, H2SO4 concentration 180g / L, temperature 30℃, current density 1500A / m 2 , time is 3s.
[0106] S4: The process parameters of secondary curing are: in the electrolyte, Cu 2+ Concentration 45g / L, H2SO4 concentration 180g / L, temperature 30℃, current density 300A / m 2 , time is 3s.
[0107] S5: The process parameters of the antioxidant process are: in the electrolyte, benzotriazole 8g / L, barium dinonylnaphthalenesulfonate 10g / L, tocopherol 5g / L, pH 7, temperature 50℃, current density 800A / m 2 , time is 4s.
[0108] S6: The process parameters of the heat-resistant process are: in the electrolyte, Zn 2+ Concentration 10g / L, Ni 2+ Concentration 10g / L, Pt 2+ Concentration 0.005g / L, Ta 5+ Concentration 0.005g / L, pH 8, temperature 25°C, current density 300A / m 2 , time is 4s.
[0109] S7: The process parameters of the hot water washing process are: temperature 50°C, pressure 0.1MPa.
[0110] S8: Coupling process: Phenyl triethoxysilane and γ-glycidyloxypropyl trimethoxysilane are mixed at a mass ratio of 3:1 to prepare a 0.5 wt % solution. The surface of the copper foil treated with the anti-oxidation layer is sprayed with the silane coupling agent aqueous solution.
[0111] S9: Drying: Drying at a temperature of 80°C for 10 seconds to obtain a finished foil.
[0112] Comparative Example 2
[0113] A high temperature resistant electrolytic copper foil, the preparation method is as follows:
[0114] The electrolytic process is used to prepare the 13-14μm rough foil, and then different electrolyte combinations and electrodeposition process parameters are used in the electrolytic equipment in multiple stages to treat the surface of the electrolytic copper foil: including acidification, roughening process, curing process, anti-oxidation process, heat-resistant process, hot water washing process, coupling process and drying. The process flow is as follows:
[0115] Compared with Example 1, the only difference is S5:
[0116] The process parameters of the antioxidant process are: in the electrolyte, 13.8 g / L of benzotriazole, 9.2 g / L of barium dinonylnaphthalenesulfonate, pH 7, temperature 50 °C, current density 800 A / m 2 , time is 4s.
[0117] The remaining operations are the same as those in Example 1.
[0118] Comparative Example 3
[0119] A high temperature resistant electrolytic copper foil, the preparation method is as follows:
[0120] The electrolytic process is used to prepare the 13-14μm rough foil, and then different electrolyte combinations and electrodeposition process parameters are used in the electrolytic equipment in multiple stages to treat the surface of the electrolytic copper foil: including acidification, roughening process, curing process, anti-oxidation process, heat-resistant process, hot water washing process, coupling process and drying. The process flow is as follows:
[0121] Compared with Example 1, the only difference is S5:
[0122] S5: The process parameters of the antioxidant process are: in the electrolyte, barium dinonylnaphthalenesulfonate 15.3 g / L, tocopherol 7.7 g / L, pH 7, temperature 50 °C, current density 800 A / m 2 , time is 4s.
[0123] The remaining operations are the same as those in Example 1.
[0124] Comparative Example 4
[0125] A high temperature resistant electrolytic copper foil, the preparation method is as follows:
[0126] The electrolytic process is used to prepare the 13-14μm rough foil, and then different electrolyte combinations and electrodeposition process parameters are used in the electrolytic equipment in multiple stages to treat the surface of the electrolytic copper foil: including acidification, roughening process, curing process, anti-oxidation process, heat-resistant process, hot water washing process, coupling process and drying. The process flow is as follows:
[0127] Compared with Example 1, the only difference is S5:
[0128] The electrolyte contained 17.25 g / L benzotriazole, 5.75 g / L tocopherol, pH 6, temperature 40°C, and current density 450 A / m 2 , time is 2s.
[0129] The remaining operations are the same as those in Example 1.
[0130] Comparative Example 5
[0131] A high temperature resistant electrolytic copper foil, the preparation method is as follows:
[0132] The electrolytic process is used to prepare the 13-14μm rough foil, and then different electrolyte combinations and electrodeposition process parameters are used in the electrolytic equipment in multiple stages to treat the surface of the electrolytic copper foil: including acidification, roughening process, curing process, anti-oxidation process, heat-resistant process, hot water washing process, coupling process and drying. The process flow is as follows:
[0133] Compared with Example 1, the only difference is S6:
[0134] S6: The process parameters of the heat-resistant process are: in the electrolyte, Zn 2+ Concentration 5.03g / L, Ni 2+ Concentration 4.02g / L, Pt 2+ Concentration 0.05g / L, pH 8, temperature 40°C, current density 180A / m 2 , time is 2s.
[0135] Comparative Example 6
[0136] A high temperature resistant electrolytic copper foil, the preparation method is as follows:
[0137] The electrolytic process is used to prepare the 13-14μm rough foil, and then different electrolyte combinations and electrodeposition process parameters are used in the electrolytic equipment in multiple stages to treat the surface of the electrolytic copper foil: including acidification, roughening process, curing process, anti-oxidation process, heat-resistant process, hot water washing process, coupling process and drying. The process flow is as follows:
[0138] Compared with Example 1, the only difference is S6:
[0139] S6: The process parameters of the heat-resistant process are: in the electrolyte, Zn 2+ Concentration 5.03g / L, Ni 2+ Concentration 4.02g / L, Ta 5+ Concentration 0.05g / L, pH 8, temperature 40°C, current density 180A / m 2 , time is 2s.
[0140] Comparative Example 7
[0141] A high temperature resistant electrolytic copper foil, the preparation method is as follows:
[0142] The electrolytic process is used to prepare the 13-14μm rough foil, and then different electrolyte combinations and electrodeposition process parameters are used in the electrolytic equipment in multiple stages to treat the surface of the electrolytic copper foil: including acidification, roughening process, curing process, anti-oxidation process, heat-resistant process, hot water washing process, coupling process and drying. The process flow is as follows:
[0143] Compared with Example 1, the only difference is S6:
[0144] S6: The process parameters of the heat-resistant process are: in the electrolyte, Zn 2+ Concentration 5.03g / L, Ni 2+ Concentration 4.02g / L, Ta 5+ Concentration 0.05g / L, pH 8, temperature 40°C, current density 180A / m 2 , time is 2s.
[0145] Comparative Example 8
[0146] A high temperature resistant electrolytic copper foil, the preparation method is as follows:
[0147] The electrolytic process is used to prepare the 13-14μm rough foil, and then different electrolyte combinations and electrodeposition process parameters are used in the electrolytic equipment in multiple stages to treat the surface of the electrolytic copper foil: including acidification, roughening process, curing process, anti-oxidation process, heat-resistant process, hot water washing process, coupling process and drying. The process flow is as follows:
[0148] Compared with Example 1, the only difference is S6:
[0149] S6: The process parameters of the heat-resistant process are: in the electrolyte, Zn 2+ Concentration 2.275g / L, Ni 2+ Concentration 2.275g / L, Pt 2+ Concentration 2.275g / L, Ta 5+ Concentration 2.275g / L, pH 8, temperature 40°C, current density 180A / m 2 , time is 2s.
[0150] Comparative Example 9
[0151] A high temperature resistant electrolytic copper foil, the preparation method is as follows:
[0152] The electrolytic process is used to prepare the 13-14μm rough foil, and then different electrolyte combinations and electrodeposition process parameters are used in the electrolytic equipment in multiple stages to treat the surface of the electrolytic copper foil: including acidification, roughening process, curing process, anti-oxidation process, heat-resistant process, hot water washing process, coupling process and drying. The process flow is as follows:
[0153] Compared with Example 1, the only difference is S8:
[0154] S8: Coupling process: Prepare a 0.32 wt% solution of coupling agent phenyltriethoxysilane. Spray the silane coupling agent aqueous solution on the surface of the copper foil treated with the anti-oxidation layer.
[0155] Comparative Example 10
[0156] A high temperature resistant electrolytic copper foil, the preparation method is as follows:
[0157] The electrolytic process is used to prepare the 13-14μm rough foil, and then different electrolyte combinations and electrodeposition process parameters are used in the electrolytic equipment in multiple stages to treat the surface of the electrolytic copper foil: including acidification, roughening process, curing process, anti-oxidation process, heat-resistant process, hot water washing process, coupling process and drying. The process flow is as follows:
[0158] Compared with Example 1, the only difference is S8:
[0159] S8: Coupling process: The coupling agent γ-glycidyloxypropyltrimethoxysilane is prepared into a 0.32 wt % solution. The surface of the copper foil treated with the anti-oxidation layer is sprayed with the silane coupling agent aqueous solution.
[0160] Test Example 1
[0161] Test method:
[0162] 1. The peel strength of the electrolytic copper foils obtained in Examples 1-3 and Comparative Examples 1-10 under a normal environment (temperature of 24° C., humidity of 52%) was measured and recorded as the peel strength under normal conditions.
[0163] 2. The electrolytic copper foils obtained in Examples 1-3 and Comparative Examples 1-10 were placed in a drying oven at 380°C for 90 minutes. The electrolytic copper foils after the drying oven treatment were taken out to measure the peeling strength, which was recorded as the peeling strength at 380°C.
[0164] 3. The electrolytic copper foils obtained in Examples 1-3 and Comparative Examples 1-10 were placed in a constant temperature box and maintained at a temperature of 25°C and a humidity of 99% for 5 hours. The electrolytic copper foils after treatment in the constant temperature box were taken out to measure the peel strength, which was recorded as the peel strength under 99% humidity conditions.
[0165] 4. The electrolytic copper foils obtained in Examples 1-3 and Comparative Examples 1-10 were immersed in sulfuric acid with a mass concentration of 70%. After 25 minutes, the electrolytic copper foils immersed in sulfuric acid were taken out to measure the peeling strength, which was recorded as the peeling strength under acidic conditions.
[0166] 5. The electrolytic copper foils obtained in Examples 1-3 and Comparative Examples 1-10 were immersed in ammonia water with a mass concentration of 55%. After 30 minutes, the electrolytic copper foils immersed in ammonia water were taken out to measure the peeling strength, which was recorded as the peeling strength under alkaline conditions.
[0167] 6. The heat resistance test is carried out in a 288°C solder bath to test whether the electrolytic copper foils obtained in Examples 1-3 and Comparative Examples 1-10 have bubbles within 30 seconds.
[0168] Table 1. Test results
[0169]
[0170]
[0171] As can be seen from Table 1, the heat resistance of the electrolytic copper foil obtained by the specific preparation method of the present invention is significantly improved. This is because the present invention optimizes the anti-oxidation layer treatment, uses benzotriazole, barium dinonylnaphthalenesulfonate and tocopherol as the anti-oxidation layer, and finds that the three have a synergistic effect, and significantly improves the normal temperature and high temperature oxidation resistance of the obtained electrolytic copper foil under a specific ratio, as well as its high temperature peeling strength. By optimizing the heat-resistant layer treatment, a quaternary alloy heat-resistant layer is formed with zinc, nickel, platinum and tantalum. Under a specific ratio, not only can the normal temperature and high temperature oxidation resistance of the obtained electrolytic copper foil be significantly improved, as well as its high temperature peeling strength, but also the pressure on cost is alleviated. The present invention uses dodecyl trimethyl ammonium chloride and γ-glycidyl ether oxypropyl trimethoxy silane as coupling agents, and under a specific ratio, the combination of the electrolytic copper foil is made tighter and the peeling strength is stronger.
[0172] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a high temperature resistant electrolytic copper foil, characterized in that: It includes a roughening process, a curing process, an anti-oxidation process, a heat-resistant process, a hot water washing process and a coupling process; wherein the electrolyte of the anti-oxidation process contains benzotriazole, barium dinonylnaphthalenesulfonate and tocopherol, and the mass ratio of the three is 1-3:0.8-1.5:0.1-1.
2. The preparation method according to claim 1, characterized in that: The roughening process includes primary roughening and secondary roughening.
3. The preparation method according to claim 2, characterized in that: The process parameters of the primary roughening are: in the electrolyte, Cu 2+ Concentration 20-30g / L, H2SO4 concentration 190-210g / L, temperature 20-25℃, current density 800-1200A / m 2 , time is 4-6s.
4. The preparation method according to claim 2, characterized in that: The process parameters of the secondary roughening are: in the electrolyte, Cu 2+ Concentration 20-30g / L, H2SO4 concentration 190-210g / L, temperature 20-25℃, current density 500-800A / m 2 , time is 1-3s.
5. The preparation method according to claim 1, characterized in that: The curing process includes primary curing and secondary curing.
6. The preparation method according to claim 5, characterized in that: The process parameters of the one-step curing are: in the electrolyte, Cu 2+ Concentration 35-42g / L, H2SO4 concentration 140-160g / L, temperature 20-25℃, current density 800-1000A / m 2 , time is 4-6s.
7. The preparation method according to claim 5, characterized in that: The process parameters of the secondary curing are: in the electrolyte, Cu 2+ Concentration 35-42g / L, H2SO4 concentration 140-160g / L, temperature 20-25℃, current density 500-600A / m 2 , time is 1-3s.
8. The preparation method according to claim 1, characterized in that: The mass ratio of benzotriazole, barium dinonylnaphthalenesulfonate and tocopherol is 1.2-2:0.8-1.52:0.2-0.
6.
9. The preparation method according to claim 1, characterized in that: The process parameters of the anti-oxidation process are: in the electrolyte, benzotriazole 2-5g / L, barium dinonylnaphthalenesulfonate 1-3g / L, tocopherol 0.1-1.5g / L, pH 4-8, temperature 30-45°C, current density 300-500A / m 2 , time is 1-3s.
10. The preparation method according to claim 1, characterized in that: In the heat-resistant process, a heat-resistant layer is formed by zinc, nickel, platinum and tantalum in the electrolyte.
11. The preparation method according to claim 10, characterized in that: The mass ratio of zinc, nickel, platinum and tantalum is 8-12:6-10:0.05-0.2:0.05-0.
2.
12. The preparation method according to claim 1, characterized in that: The process parameters of the heat-resistant process are: in the electrolyte, Zn 2+ 3-8g / L, Ni 2+ 1-6g / L, Pt 2+ 0.01-0.1g / L, Ta 5+ 0.01-0.1g / L, pH 7-9, temperature 30-45℃, current density 140-220A / m 2 , time is 1-3s.
13. The preparation method according to claim 1, characterized in that: The coupling agent in the coupling step is a silane coupling agent.
14. The preparation method according to claim 13, characterized in that: The silane coupling agent is selected from at least one of phenyltriethoxysilane and γ-glycidyloxypropyltrimethoxysilane.
15. The preparation method according to claim 14, characterized in that: The silane coupling agent is phenyltriethoxysilane and γ-glycidyloxypropyltrimethoxysilane; the mass ratio of phenyltriethoxysilane to γ-glycidyloxypropyltrimethoxysilane is 1-2:0.8-1.
2.
16. The preparation method according to claim 13, characterized in that: The concentration of the silane coupling agent is 0.3%-0.4%.
17. The preparation method according to claim 1, characterized in that: The preparation method also includes acidification before the roughening process; the process parameters of the acidification are: H2SO4 concentration in the electrolyte is 140-190g / L, the temperature is 30-40°C, and the time is 1-3s.
18. The preparation method according to claim 1, characterized in that: The preparation method further comprises drying; the drying is performed after the coupling process, and the process parameters are: temperature 100-150°C.
19. A high temperature resistant electrolytic copper foil prepared by the preparation method according to any one of claims 1 to 18.
20. Use of the high temperature resistant electrolytic copper foil prepared by the preparation method according to any one of claims 1 to 18 in printed circuit boards.
Citation Information
Patent Citations
Electrolytic copper foil surface treatment process
CN105154927A
A method for preparing high heat-resistant electrolytic copper foil
CN116791160B